41 Year Long-Term Durability of High Volume Blast-Furnace Slag Cement Concrete - Dan, Yasuhiro; Kurata, Kazuhide; Ohtsuka, Yusuke; Hashimoto, Manabu (Journal of Advanced Concrete Technology, 2021)
In this study, we investigated the durability of high-volume ground granulated blast furnace slag (GGBS) blended cement concrete containing over 70% of GGBS for possible general structural applications. The concrete specimens used were exposed to natural outdoor conditions for 41 years on a building rooftop. The following is found. The exposed top surface of concrete with 88.5% GGBS 4000 replacement, the exposed top surface and the corners of sulfated slag cement showed peel failure of the paste, but the specimens of concrete with 68.5% GGBS 4000 and GGBS 2000 replacement were in sound condition. The compressive strength of all mix proportions did not decrease significantly over 41 years. The carbonation depth of concrete specimens containing 70% GGBS was about 7 to 9 mm, and about 15 mm for specimens containing 90% GGBS. Despite the high volume of GGBS content (70%) in the concrete specimens, traces of Ca(OH)2, which is involved in the chemical reaction of GGBS, were found in parts that remained uncarbonated. Ca(OH)2 increases the alkalinity of the specimen and is thus considered to have a rebar corrosion-inhibiting effect. This paper is the English translation from the authors’ previous work [Hashimoto, M., et al., (2019). “A study on the long-term durability of high-volume bast-furnace slag cement concrete for 41 years.” Concrete Research and Technology, Vol.30, pp.77-84. (in Japanese)].